Sotos' Syndrome (Cerebral Gigantism) with Peripheral Dysostosis - Evans, P. R. (1971)
A girl had short stumpy hands and feet due to osseous dystrophy; in other respects she showed all the main and many of the minor features of Sotos' syndrome during infancy. Then she was on the 97th centile for height, but she grew to be a woman on the 10th centile. Menarche was at 12¾ years; growth in height stopped before 14½ though epiphysial fusion had not occurred; educational difficulties were still being fought at 18 years but she was well adjusted and happy.